THE EFFECT OF PROFITABILITY, CASH HOLDING, COMPANY SIZE, AND FINANCIAL LEVERAGE ON INCOME SMOOTHING WITH GCG AS A MODERATING VARIABLE - Arisandy, Rajulan; Lutfi, Ardhani (I-Economics, 2024)
This study aims to analyze the influence of profitability, cash holding, company size, and financial leverage on income smoothing practices among technology sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Additionally, it examines the moderating role of good corporate governance (GCG) in strengthening the impact of these four variables on income smoothing. Using a quantitative approach, purposive sampling, and logistic regression analysis, the results show that profitability, cash holding, company size, and financial leverage do not significantly affect income smoothing. Furthermore, the implementation of GCG does not moderate the influence of these variables on income smoothing.